Memorandum of particular points of life insurance practice, deliberated upon at a meeting of the managers of all the Scottish offices, held at Edinburgh on 19th November 1840 (Johnstone, 1840)
Also contains : Rates of extra premiums for foreign climates, agreed to be adopted by all the life assurance offices of Scotland.